VOVINAM VIĘT VO DAO – tradition and history - Gheorghe Pricop; Thierry Long (Annals of the “Ştefan cel Mare” University: Physical Education and Sport Section - The Science and Art of Movement, 2019)
Vovinam is a type of Vietnamese martial arts. Vovinam is practiced with and without weapons. It is based on the principle of harmony between hard and soft. It includes training of the body as well as the mind. It uses force and reaction of the opponent. The name is a portmanteau of Vo (Võ): meaning "Martial Arts" and Vinam standing for "Vietnam". The VOVINAM Vięt Vo Dao is a martial discipline which must be understood as one of the fundamental components of the human culture. The VOVINAM Vięt Vo Dao proclaims indeed, the physical and mental training of the individual who symbolizes ideal, perfection, kindness and progress, having the welfare of the society for an object.